2010
DOI: 10.2134/agronj2009.0390
|View full text |Cite
|
Sign up to set email alerts
|

Tillage, Seeding, and Nitrogen Rate Effects on Rice Density, Yield, and Yield Components of Two Rice Cultivars

Abstract: Research was conducted for 2 yr on a Crowley silt loam soil (fi ne, smectitic, thermic Typic Albaqualfs) near Crowley, LA to evaluate the main eff ects of tillage, seeding and N rate and potential interactions on rice (Oryza sativa L.) density, yield, and yield components. Two tillage systems (conventional and fall-stale seedbed), four seeding rates (162, 323, 484, and 646 seed m -2 ) and four N rates (101, 134, 168, and 202 kg ha -1 ) were evaluated. 'Jupiter' and 'Cheniere' a medium and long grain cultivar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
3
16
1
Order By: Relevance
“…All the previous studies mentioned in the previous paragraph are unanimous in showing the positive relation between panicles/m 2 and plant density. The same response was found by Harrell and Blanche (2010) for direct seeded rice in the USA and by Nakano et al (2012) for a Japanese highyielding rice for feed use. Huang et al (2013) reported an exceptional case for Chinese hybrid varieties that while the effect of plant density on panicles/m 2 was positive and significant for crops planted early, no significant relation was found for crops planted late.…”
Section: Response-function Estimationsupporting
confidence: 74%
See 2 more Smart Citations
“…All the previous studies mentioned in the previous paragraph are unanimous in showing the positive relation between panicles/m 2 and plant density. The same response was found by Harrell and Blanche (2010) for direct seeded rice in the USA and by Nakano et al (2012) for a Japanese highyielding rice for feed use. Huang et al (2013) reported an exceptional case for Chinese hybrid varieties that while the effect of plant density on panicles/m 2 was positive and significant for crops planted early, no significant relation was found for crops planted late.…”
Section: Response-function Estimationsupporting
confidence: 74%
“…The effects of plant density could be different if plant density is measured in terms of row spacing or seeding rate. Although Lampayan et al (2010) and Chauhan and Posner (2011), both of which adopted row spacing, and Harrell and Blanche (2010), which used seeding rate, report plant-density responses the patterns of which are essentially the same as those reported by the studies, including ours, which adopted the hill density, further research is needed to confirm differences in the effects of plant density among the different measures of plant density.…”
Section: Comparison With Farmers' Actual Practicesmentioning
confidence: 54%
See 1 more Smart Citation
“…However, more recent research indicates that rice uses N more effi ciently and produces greater grain yields when applied in a single prefl ood application (Bollich et al, 1994;Norman et al, 2000;Slaton et al, 2003;Bond et al, 2008). Applying high rates of N in a single application can cause unwanted agronomic eff ects such as greater plant height which can result in potential grain yield loss due to lodging (Gravois and Helms, 1996;Slaton et al, 2003;Bond et al, 2008;Harrell and Blanche, 2010).…”
mentioning
confidence: 99%
“…Recommended seeding rates for Louisiana rice production vary by variety, but range from 215 to 323 seeds m -2 . Th is allows for a fi nal plant population density of 108 to 161 seedlings m -2 (Saichuck et al, 2008;Harrell and Blanche, 2010). Research with older inbred cultivars suggests low seeding rates do not negatively impact grain yield (Jones and Snyder, 1987;Gravois and Helms, 1992;Ottis and Talbert, 2005;Harrell and Blanche, 2010) largely due to greater levels of tillering at low seeding rates (Schnier et al, 1990;Counce et al, 1992).…”
mentioning
confidence: 99%